2019
DOI: 10.1590/0001-3765201920180244
|View full text |Cite
|
Sign up to set email alerts
|

Trophic dynamics (Dissolved Inorganic Nitrogen-DIN and Dissolved Inorganic Phosphorus-DIP) in tropical urban estuarine systems during periods of high and low river discharge rates

Abstract: Inorganic Nitrogen-DIN and Dissolved Inorganic Phosphorus-DIP) in tropical urban estuarine systems during periods of high and low river discharge rates. An Acad Bras Cienc 91: e20180244.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Further examination of the results revealed that winter acted as a phosphate sink, while the bay served as a phosphate source during the other three seasons, with autumn exhibiting the highest phosphate output. The daily average discharge of SRP into the bay stood at 21.74 kg/d, lower than that of Shenzhen Bay and Pernambuco, Brazil [1,67]. Additionally, the annual groundwater input of SRP in the study area was 6.16 kg/d [34], surpassing the amount of SRP discharged into the bay via surface rivers in winter.…”
Section: Analysis Of the Characteristics Of Nutrient Balance In Dapen...mentioning
confidence: 74%
“…Further examination of the results revealed that winter acted as a phosphate sink, while the bay served as a phosphate source during the other three seasons, with autumn exhibiting the highest phosphate output. The daily average discharge of SRP into the bay stood at 21.74 kg/d, lower than that of Shenzhen Bay and Pernambuco, Brazil [1,67]. Additionally, the annual groundwater input of SRP in the study area was 6.16 kg/d [34], surpassing the amount of SRP discharged into the bay via surface rivers in winter.…”
Section: Analysis Of the Characteristics Of Nutrient Balance In Dapen...mentioning
confidence: 74%
“…These contaminants can directly affect the abundance and diversity of meiofauna ( Moens et al, 2014 ). Additionally, agricultural fertilizer can be observed ( Noriega et al, 2019 ) which can cause eutrophication and anoxia due to bacterial proliferation ( Carriço et al, 2013 ). Furthermore the input of tributyltin ( Maciel et al, 2018 ) can interrupt faunal reproductive processes and cause juvenile deaths ( Schratzberger et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…inputs from rivers (Noriega et al, 2019). In the case of the Paraguaçu River estuary, the influence of the Pedra do Cavalo dam that controls the flow of freshwater in the estuarine gradient must be considered, which ats as a physical barrier, retaining the material in the river channel.…”
Section: Discussionmentioning
confidence: 99%